Analysis of Signalless Four-way Intersection Congestion at Jalan Kyai Sampang, Demak Regency - Hakim, Daffa Nurul; Rizal, Khoirur (Jurnal Civil Engineering Study, 2023)
An intersection is a part of a road segment where currents from various directions or directions intersect. This results in congestion along the intersection arm. This intersection is located in the center of Demak Regency, an unsignalized intersection with 4 arms on Jalan Kyai Sampang, Jalan Kyai Singkil, Jalan Sultan Fatah towards Kudus and Jalan Sultan Fatah towards Semarang which is located in the market area, offices, residential areas and schools. This research was conducted to determine the performance of the intersection, especially with regard to the operational conditions of the intersection as indicated by the value of capacity, degree of saturation, delay, and queuing opportunities. Then after the analysis, it is also obtained that the capacity value at the intersection is 1634 smp/hour. Analysis of the value of the degree of saturation (DS) obtained DS results amounted to 0.79 smp/hour. Delay analysis (D) results in a delay of 13.33 smp/hour. Then the analysis of queuing opportunities obtained the results of queuing opportunities of 64.6% - 132.5%.